1995
DOI: 10.1017/cbo9780511664700
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Industrial Competition

Abstract: The Dynamics of Industrial Competition, first published in 1995, describes the internal dynamics of industries using longitudinal data that make it possible to track firms over time. It provides a comprehensive picture of a number of different aspects of firm turnover in North America that arise from the competitive process - the entry and the exit of firms, the growth and decline of incumbent firms, and the merger process. Instantaneous and cumulative measures of market dynamics are provided by examining chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
176
1
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(193 citation statements)
references
References 0 publications
8
176
1
8
Order By: Relevance
“…Since the two agents discount cash flows at the same rate, the optimal contract 6 As shown below, there is an incentive compatible and feasible contract for any V ≥ 0.…”
Section: A Benchmark: Contracts Under Symmetric Informationmentioning
confidence: 99%
“…Since the two agents discount cash flows at the same rate, the optimal contract 6 As shown below, there is an incentive compatible and feasible contract for any V ≥ 0.…”
Section: A Benchmark: Contracts Under Symmetric Informationmentioning
confidence: 99%
“…Many new businesses fail shortly after inception (Baldwin, 1995;Dunne et al, 1988) and entrepreneurship is a career choice that does not, on average, o¤er improved …nancial remuneration compared to alternatives. Hamilton (2000) has shown that, except for the highest 25% of entrepreneurial incomes, remaining in a wage-producing job (or moving back to it) makes more economic sense than starting a new business.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, more productive entrants can appear less profitable when prices are not observed. 9 For evidence on the cross-cohort and within-cohort productivity distribution, see Baldwin (1995), Balk andGort (1993), Foster, Haltiwanger andSyverson (2003). For evidence on cohort productivity dynamics, see Balk and Gort (1993) and Jensen, McGuckin and Stiroh (2000).…”
Section: Introductionmentioning
confidence: 99%